Development of Digital Platform-Based Learning Media for Short Story Texts for Grade XI High School - Lestari, Suci; Murtadho, Fathiaty; Eriyani, Reni Nur (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study focuses on the development of digital platform-based learning media for short story text material for grade XI SMA/MA. The aim is to overcome students' difficulties in understanding the material and improve the effectiveness of Indonesian language learning. The method used is structured research and development based on the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). In this study, data analysis combines quantitative and qualitative techniques obtained through questionnaires. Validation was carried out by media expert validators, material experts, and Indonesian language teachers. The results of the media expert validation obtained 87%, material experts 96% and Indonesian language teachers 98%. Then, the assessment was carried out by students obtaining 90%. This digital platform-based learning media offers an alternative for teachers to support the learning process. The implication is to provide more flexible access to learning materials, thereby encouraging independent learning. Thus, digital platform-based learning media for short story texts is considered feasible, so that it can be applied in the classroom.